Assessment of the quality of products of road maintenance organizations - Dogadaylo, Yana; Man’ko, Margarita (Sienciea Scripts, 2021)
The monograph reflects the results of the research, the purpose of which was to clarify the theoretical and methodological basis for assessing the quality of works and products of road maintenance enterprises. As a result, the solution of the problem was clarified the essence of the concept "quality of road products ' the quality as an object of the road economy was studied; the analysis of quality management methods and quality assessment of road works was done; the most appropriate method for assessing the quality of road robots was chosen. To implement it, the methodological approach to the deployment of quality function through its adaptation to the economic conditions of road maintenance organizations, based on the implementation of not eight but seven stages of structuring the quality function and determine the consumer's requirements for road works and their characteristics has been improved. The primary requirements are comfort and safety of traffic, continuity of traffic, speed of traffic, capacity and load level, permissible dimensions and level of road service. The proposed developments will allow road organizations to perform works according to the priority requirements of consumers. Dogadaylo Yana Viktorovna, PhD in Economics, assistant professor of Management department of Kharkov National Automobile and Road University.
Keywords: quality management; controlling; budgeting; project management and ensuring the effectiveness of the enterprise